Development of new heat exchanger design for the use of exhaust gases of ice in cogeneration plants. Hydraulic calculation - Gorobets, V.; Trokhanyak, V.; Antipov, I.; Gorobets, Yu. (Energy and Automation, 2025)
New design of heat exchanger for utilization of exhaust gases of an internal combustion engine, which is part of cogeneration plant, is proposed. This design differs from traditional designs by the presence of compact bundles of small diameter pipes in the absence of gaps between adjacent pipes in the longitudinal direction of gas coolant. Method of hydraulic calculation of heat exchanger-utilizer has been developed, which makes it possible to determine the power of smoke exhauster when removing combustion products and pump for pumping water coolant. It was found that new design of heat exchanger has significantly lower pressure losses in the intertube channel of heat exchanger-utilizer compared to known designs. Capacities of smoke exhauster and water pump have been determined, which can be used when selecting heat energy equipment for cogeneration plants based on internal combustion engines.